APLIKASI SISTEM PENDUKUNG KEPUTUSAN TANAMAN OBAT HERBAL UNTUK BERBAGAI PENYAKIT DENGAN METODE ROC (RANK ORDER CENTROID) DAN METODE ORESTE BERBASIS MOBILE WEB - Nella Astiani; Desi Andreswari; Yudi Setiawan (Universitas Kristen Duta Wacana, 2016)
Herbal medicinal plant is a traditional medicinal plant that is used to cure a disease. Most of modern people did not know yet the benefits that will be gotten from herbal plants for the health. This research developed a supporting decision application system of herbal medicinal plants for various diseases. ROC (Rank Order Centroid) method was used to count the total number of criteria value and Oreste method was used to rank the alternative herbal medicinal plants with criteria which influence it, namely disease, blood pressure, tall, weight, user’s condition (other diseases), age, kinds of plants, substance and efficacy of plants themselves. Final result of this system was that there were some alternative herbal medicinal plants which were appropriate to user’s disease. In this research, the researcher conducted white box testing by using path base testing to make complex logical estimates to define current action and conducted black box testing by using equivalence partitioning technique which divided domain input, decided testing case by explaining kinds of mistakes. The results of proper test for the system which were done by using questionnaire were gotten 86.75% for testing of functional system, 87% for interface and accessing testing, and 87.33% for testing of advantages system.